Electric discharge hole grinding in hybrid metal matrix composite. Issue 2 (25th January 2017) - Kumar, Ravinder; Singh, Abhishek; Singh, Inderdeep
ABSTRACT: Moving toward a hybrid approach, a hybrid process, electric discharge hole grinding (EDHG) was used to machine a hybrid metal matrix composite (MMC) (Al6063/SiC/Al2 O3 /Gr). Here, holes were drilled and ground in a single step process (EDHG) using a novel tool electrode. The experiments were designed using response surface methodology (RSM). The objective of this study was to investigate the effect of electric discharge diamond hole grinding operation on the surface roughness (SR) of the hole. The input process parameters were current, duty factor, tool speed and flushing pressure. It was found that the process is very effective in producing a finished hole. A comparison of surface roughness was made between electric discharge drilling (EDD) and electric discharge diamond hole grinding, thereby showing the effectiveness of the electric discharge diamond hole grinding process. The grinding action of the process is clearly visible in the scanning electron microscopic (SEM) image. It was observed that the craters, globules of resolidified material and micro cracks, which are normally seen on surfaces machined by electric discharge machining (EDM), are completely ground off by electric discharge diamond hole grinding.